PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PERKOSAAN BAGI PENYANDANG DISABILITAS - Fadhilah, Rakha; Farhana, Farhana (Universitas Stikubank, 2024)
Sexual violence against persons with disabilities, especially women, is increasing due to their vulnerability. This research is a normative legal research, using a case approach. The data source used is secondary data, namely primary legal materials, such as laws and court decisions. Secondary data used includes literature related to the object of research. The method used is the normative juridical method. The results of this study found that although the protection and consideration of judges are quite good, there are still factors that need to be considered, especially the rights of victims in accordance with Law No. 8 of 2016. One example is the decision that will be discussed in this article, namely Decision No. 42/Pid.B/2019/PN.Lbb.